How high‐fat diet affects bone in mice: A systematic review and meta‐analysis. (12th July 2022) - Zhang, Zheng; Zhang, Zhanrong; Pei, Lei; Zhang, Xiaozhou; Li, Boyuan; Meng, Yichen; Zhou, Xuhui
Summary: High‐fat diet (HFD) feeding for mice is commonly used to model obesity. However, conflicting results have been reported on the relationship between HFD and bone mass. In this systematic review and meta‐analysis, we synthesized data from 80 articles to determine the alterations in cortical and trabecular bone mass of femur, tibia, and vertebrae in C57BL/6 mice after HFD. Overall, we detected decreased trabecular bone mass as well as deteriorated architecture, in femur and tibia of HFD treated mice. The vertebral trabecula was also impaired, possibly due to its reshaping into a more fragmentized pattern. In addition, pooled cortical thickness declined in femur, tibia, and vertebrae. Combined with changes in other cortical parameters, HFD could lead to a larger femoral bone marrow cavity, and a thinner and more fragile cortex. Moreover, we conducted subgroup analyses to explore the influence of mice's sex and age as well as HFD's ingredients and intervention period. Based on our data, male mice or mice aged 6–12 weeks old are relatively susceptible to HFD. HFD with > 50% of energy from fats and intervention time of 10 weeks to 5 months are more likely to induce skeletal alterations. Altogether, these findings supported HFD as an appropriate model for obesity‐associated bone loss and can guide future studies.